Desempenho cognitivo e discurso narrativo após internação por SARS-CoV-2 - Souza, Franklim Oliveira (2024)
Introduction:The COVID-19 pandemic was and has been a major challenge for healthcare systems around the world. This causes sequelae that range from severe acute respiratory syndrome, cardiovascular problems, and cognitive impairment. The latter is not yet widely known, making it necessary to understand such losses to improve the quality of life of infected people. Objective: To characterize cognitive and narrative speech performance after SARSCoV-2 infection. Method: This is a cross-sectional study of an exploratory nature, conducted with people who were infected by SARS-CoV-2 and were hospitalized at the university hospital in the city of Lagarto and Aracaju. The sample consisted of 32 participants living in Sergipe, of any gender and over 18 years old. People who at some point during the research withdrew their free and informed consent were excluded; who had difficulty answering the questionnaires orally; with cognitive deficiencies prior to hospitalization; bed-ridden due to difficulty in moving around to participate in the research; who tested positive for COVID-19 at the time of the assessments; and who used psychoactive drugs (including sleeping pills) not prescribed by a doctor. Participants underwent a battery of assessments, starting with anamnesis, which collected information on socioeconomic, identification and speech-language pathology complaints before and after Covid-19 infection. For cognitive screening, the reduced version of the Red Mini Mental State Examination was used. Cognitive function was assessed using the Brief Neuropsychological Assessment Instrument – Neupsilin, which can be applied to people aged 12 to 90, whether neurologically healthy or not, and speech was assessed using the Montreal Toulouse Language Assessment Battery Instrument which It is made up of 22 tasks that feature oral and graphic emission, oral and graphic comprehension, in addition to nonverbal praxis and calculation. Results: Of the 32 participants, 75% were male and 25% female. The average age was 54.77, with 3.77 years of education. Speech was found to be altered in 53.13%, among the cognitive skills analyzed in this study, verbal fluency was the one that showed the highest percentage of change with 53.13%, followed by auditory span with 50%, digit ordering with 46.87% and working memory with 43.75%. Conclusion: It is concluded that participants infected by SARS-CoV-2 and who required hospitalization in the municipalities of Lagarto and Aracaju located in the state of Sergipe, presented changes in speech and cognitive aspects related to verbal fluency, auditory span, ordering of digits and working memory. Furthermore, it was observed that changes in discursive skills were positively correlated with cognitive aspects such as working memory and verbal fluency.